Análise e parametrização de modelos empíricos da radiação de onda longa no Pantanal mato-grossense - Carrilho, Soilce Beatriz de Paula (2018)
The objective of this work was to evaluate the models for the estimation of long-wave (Ld) radiation in the Mato Grosso Pantanal, considering the sky cover in the clear sky conditions. Taking into account that measurements of Ld are rare, and that this parameter is almost always obtained indirectly through several models available in the literature, it is opted in this work, to analyze 29 models for the estimation of Ld. Data were obtained through equipment installed in a tower 28 meters on the Baia das Pedras - Pantanal in the municipality of Poconé - MT, from January to December 2013. From the estimates of Ld obtained from these formulations, those with the best performance were those with the lowest statistical errors and the highest coefficients, such as those of determination (r2), of Pearson's correlation (r), indicating a very strong correlation between the estimated values and the measured, the best indexes of agreement (d) and, consequently, the best indexes of performance (c). Of the 29 models analyzed, 44.8% had a "SOFRÍVEL" performance, 24.1% "PÉSSIMO", 17.2% "MAU", 6.9% "MÉDIO", 6.9% "BOM" and 0% with performances "ÓTIMO" and "MUITO BOM". In this analysis, it can be observed that the long wave irradiance estimation model that, in its original formulation and after its parametrization, presented the best statistical indices and, therefore, the one that best adapted to the Pantanal of Mato Grosso, for the studied period and for the conditions of clear sky, was the model BLISS (1961).